The Policy Effectiveness and Citizen Feedback of Transferable Development Rights (TDR) Program in China: A Case Study of the Chongqing Land Ticket Model - Hongwei Zhang; Linhong Ji; Hui Wang (Land)
Over the past decade, the Chongqing land ticket model has played a pivotal role in the market-oriented reform of rural land factors and serves as a representative practice of the TDR program in China. This paper constructs a systematic evaluation framework from two perspectives—policy effectiveness and citizen feedback—to comprehensively understand the policy effect of this model. The study employs methods of policy texts bibliometrics and content analysis based on big data. The results indicate that the effectiveness of land ticket policies exhibit significant fluctuations, with peaks aligning with milestones in the model’s development. Policy measures are well-aligned with the goals set forth. However, policymakers in Chongqing have historically focused more on institutional construction within the land ticket model, only recently shifting attention to the protection of farmers’ rights and interests. This imbalance may have led to potential risks regarding the loss of farmers’ property rights. The analysis of citizen feedback from the online space further took into account the impact of policy content on its audience (farmers), revealing that shortening the compensation payment time rather than increasing the compensation amount is the most common and critical demand among farmers. This underscores the urgent need for a policy-related response from the government to meet farmer’s demands for “procedural justice”. Our conclusions address a gap in the existing literature by integrating policy text analysis with public opinion, thereby offering referential insights into understanding the evolutionary process, policy features, and implementation effects of TDR program in China.